Efeitos de um termo de assentimento adaptado è idade de crianças no conhecimento e atitude relatada de participantes de uma investigação clínica - Lucas Henrique Lobato de Araujo (2017)
Child assent is a baseline condition for the ethical conduct of pediatric investigations. Evidence indicates that potential children participating in clinical research may provide an assent demonstrating ignorance about research information. Empirical research suggests the need to develop interventions capable of promoting children's knowledge about researchinformation in order to guarantee ethical validity in their decision. The adaptation of the language of the Assent Form to the age has been demonstrating positive results in the knowledge of participants of pediatric researches. Studies that have evaluated these interventions, however, are scarce in worldwide, a country where the rights of researchparticipants are ensured by specific resolutions. In this scenario, this study proposes to answer the following question: does the modification of the Assent Form enhace the knowledge of participants in a pediatric research? The purpose of this research is to evaluate the effects of aModified Assent Form (adapted to the age of the participants) in the knowledge and attitudes reported of children participating in a clinical investigation. This is an experimental, longitudinal study with a quantitative approach. It was conducted in municipalities in theNortheast of Minas Gerais, with 286 participants eligible for a clinical research. Subsequently, the participants of each age group were randomly assigned to two groups: experimental and control. In the first group the assent process was carried out using a Modified Assent Form,adapted to the age of the participants, while in the second group a standard document was used. The Modified Assent Form was elaborated using the following strategies: simplification of the language and figures, songs, schemes and a comic book. These strategies have as essential characteristic the power to produce problematic experiences rather than the assimilation of ready-made knowledge. In both age groups, there were statistically significant differences between the experimental and control in the knowledge about: the purpose andduration of the investigation, the benefits and risks, the need to perform blood tests, the right to receive chemotherapy, the mode of transmission of schistosomiasis, the possibility of reinfection after treatment, and the need for an stool sample for diagnosis, in addition to having a positive attitude towards the possibility of talking to parents about the decision toparticipate in the investigation. It was verified that children aged 7 to 12 years of the experimental group presented average percentage of correct questions of 51.75%, whereas in the experimental group this value rose to 65.12% (p <0.05). In the age range of 13-15 years these values were 57.59% and 75.55%, respectively (p <0.05). There is a statisticallysignificant difference in knowledge about research information at all ages. It is concluded that the adaptation of an assent to the age of the children is an effective intervention for the dissemination of the information of an investigation.